Establishment of political and diplomatic relations between Lithuania and France in 1918-1920: Exchange of mistrust - Vilma Bukaitė (Lietuvos Istorijos Studijos)
In 1918, the Lithuanian state was re-established referring to the principle of self-determination of nations. Hence, the first Lithuanian government expected to receive the due support and recognition from the most powerful winners of World War I, including France. However, one of the most influential architects of 'New Europe', the French Prime Minister Georges Clemenceau, conceived this new Baltic state as a potential territory of democratic Russia, which the French allies seeked to restore, and later on of Poland. According to this politician who presided at the Paris Peace Conference, Lithuania was meant to become a federal part of one of these states. His rather skeptical attitude towards the statehood of Lithuania emanated from doubts as to whether a new state would be able to retain its political autonomy while bordering with Germany and the Soviet Russia; such opinion also resulted from aspirations to consolidate a 'cordon sanitaire' between the two potential enemies of France. Another important factor was the sense of mistrust with regard to the state that had been created on the Germany's occupied territory.